The Impact of Training and Development on Employee Performance in Agriculture Sector - Nurazwa Ahmad; Anita Sharmila Pillai; Tengku Nur Azila Raja Mamat; Nurul Aqilah Mhd Yusak (Research in Management of Technology and Business, 2022)
Apart from capital, employees represent as one of the most valuable assets of a company. The fates of company reputation depend on them. The performance of an employee is affected by elements such as organizational policies, working environment, training programs and development opportunities, and workforce relations. Some public and private organizations either locally or globally lack the initiative to acknowledge the significance of upgrading the employee productivity through training. Some organizations even slash first their spending budget on training when the going gets tough which result in increasing staff turnover, higher cost to re-hire new staffs and would therefore finally detrimental to the firm’s productivity and profitability. The purpose of this paper is to ascertain the level and impact of employee performance towards training and development among workers in agricultural sector. Employing the quantitative method, the result reveals a high relationship level and a positive significant relationship between the variables. The findings of this research are beneficial for organizations to map out appropriate training and development programs for their employees.